EFEKTIVITAS PEMBERIAN REBUSAN DAUN SIRSAK (ANNONA MURICATA L) UNTUK MENURUNKAN NYERI AKUT PADA GOUT ARTHITIS - sabiila, esa faticha; Parmilah, Parmilah; Suraning Wulandari, Tri (JURNAL KESEHATAN KARTIKA, 2025)
Background : Gout arthritis is a metabolic disorder caused by the deposit and accumulation of uric acid in the joints which is characterized by inflammation and stiffness so that it causes pain and pain in the joint area. Gout arthritis pain arises due to the accumulation of monosodium crystals in the veins so that inflammation and swelling occur and then pain occurs. If acute pain is not treated immediately, it will increase the intensity of pain and interfere with daily activities. Non-pharmacological methods such as pain management using a multi-disciplinary approach, namely herbal using soursop leaf decoction.can be used to overcome acute pain problems. Soursop leaves (Annona Muricata L) contain tannin, resin and crytallizable mogostine compounds that are able to overcome joint pain and reduce swelling in gout arthritis sufferers. Objective : to determine the effectiveness of giving soursop leaf decoction to reduce acute pain in gout athritis. Method : case study on 2 female respondents who suffered from gout arthritis with complaints of pain, swelling and heat in the joints. Result : after 7 days of intervention with a frequency of 2 times a day in the morning and evening, there was a decrease in the level of pain from a scale of 6 down to 1-2. Conclusion : the administration of soursop leaf decoction can reduce acute pain in gout arthritis patients.